URGENSI REKONSTRUKSI SOSIOLOGI BAGI KAJIAN CYBER SOCIETY - Husnul Muttaqin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
The rapid changes in information technology raise questions about the relevance of sociological theories in explaining the new reality of cyber society. At least, there are two important questions that must be answered by sociologists: first, what are the characteristics of cyber reality that become the new study area of sociology? Second, how should sociology been reconstructed to understand the new model of society in cyberspace? These questions will be explored through a meta-theory study. Meta-theory is intended to study the basic structre of sociological theory, especially in the form of reflective analysis of existing theories. One of itsmain concerns is determining the object of study in a particular discipline.Through meta-theory study, this research comes to two conclusions. First, virtual reality has different characters from real life. But, frequently, virtual reality is experienced by individuals like everyday life reality, or even more real than real reality. Through the characteristics of simulation, interaction, artificiality, immersion, telepresence, networked communication and anonymity, virtual reality is transformed into a part of everyday life that cannot be separated from human life. Second, facing this new reality, sociology must adjust its scientific construction. Reconstruction of sociology can be initiated by defining what are the objects of sociological studies regarding the issues of cyber society. Based on three paradigms of Ritzer, this study concludes that social fact, social definition and social behavior paradigms must be reinterpreted, especially in relation to the importance for sociological paradigms to include non-human aspects in its theoretical buildings.Perkembangan teknologi informasi yang demikian cepat memunculkan pertanyaan soal relevansi teori-teori sosiologi dalam menjelaskan realitas baru dunia cyber. Setidaknya, ada dua hal penting yang harus dijawab oleh sosiologi: pertama, bagaimana karakteristik realitas cyber yang menjadi wilayah kajian baru sosiologi? Kedua, bagaimana sosiologi harus direkonstruksi untuk dapat memahami model masyarakat baru di dunia cyber? Kedua pertanyaan tersebut akan ditelaah melalui kajian metateori. Metateori dimaksudkan untuk mengkaji struktur dasar teori sosiologi, terutama dalam bentuk analisis reflektif atas teori-teori yang sudah ada. Salah satu konsen utama kajian metateori adalah menentukan objek kajian yang dipelajari dalam satu disiplin ilmu tertentu. Penelitian ini menghasilkan beberapa kesimpulan. Pertama, realitas virtual memiliki karakter yang berbeda dengan realitas nyata dalam kehidupan sehari-hari. Hanya saja, tak jarang realitas virtual itu dialami oleh individu tak ubahnya seperti kenyataan hidup sehari-hari, atau bahkan lebih nyata dari kenyataan riil. Melalui karakter simmulation, interaction, artificiality, immersion, telepresence, networked communicationdan anonimity, realitas virtual menjelma menjadi bagian kehidupan sehari-hari yang tak dapat dipisahkan dari kehidupan manusia. Kedua, menghadapi realitas baru ini, sosiologi mau tidak mau harus menyesuaikan bangunan keilmuannya. Rekonstruksi sosiologi dapat dimulai dengan mendefinisikan apa yang sebenarnya menjadi objek kajian sosiologi masyarakat cyber. Berangkat dari tiga paradigma Ritzer, penelitian ini mengambil kesimpulan paradigma fakta sosial, definisi sosial dan perilaku sosial harus dimaknai ulang, terutama dalam kaitan dengan pentingnya paradigma sosiologi untuk menyertakan aspek non-human dalam bangunan teoritisnya.